2012
DOI: 10.1371/journal.ppat.1002466
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants and Dynamics of Hepatitis C Virus Secretion

Abstract: The current model of hepatitis C virus (HCV) production involves the assembly of virions on or near the surface of lipid droplets, envelopment at the ER in association with components of VLDL synthesis, and egress via the secretory pathway. However, the cellular requirements for and a mechanistic understanding of HCV secretion are incomplete at best. We combined an RNA interference (RNAi) analysis of host factors for infectious HCV secretion with the development of live cell imaging of HCV core trafficking to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
188
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(208 citation statements)
references
References 92 publications
(126 reference statements)
15
188
3
2
Order By: Relevance
“…Contrary to our studies, other studies have found that nocodazole treatment inhibits microtubule-dependent transport of the HCV replication complex, initiation of productive HCV infection, and, as a result, HCV RNA replication (75,77,78). Moreover, two recent reports have shown that postassembly the vesicular HCV core protein puncta traffic via microtubules and that trafficking is inhibited by nocodazole treatment (28,50). It is important to point out that all the above-mentioned studies used much higher concentrations of nocodazole that were mostly 10 to 20 times higher than the concentration that we used in our studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our studies, other studies have found that nocodazole treatment inhibits microtubule-dependent transport of the HCV replication complex, initiation of productive HCV infection, and, as a result, HCV RNA replication (75,77,78). Moreover, two recent reports have shown that postassembly the vesicular HCV core protein puncta traffic via microtubules and that trafficking is inhibited by nocodazole treatment (28,50). It is important to point out that all the above-mentioned studies used much higher concentrations of nocodazole that were mostly 10 to 20 times higher than the concentration that we used in our studies.…”
Section: Discussioncontrasting
confidence: 99%
“…We therefore turned to the TC tag-biarsenical dye labeling system that has successfully been used to label and study several viruses in live cells (reviewed in reference 49), including HCV (28,50). Compared to the GFP-core protein fusion protein strategy, this system requires insertion of only a short nucleotide sequence encoding a peptide of 12 amino acids, including the tetracysteine (TC) tag (-CCXXCC-), into the viral genome without affecting virus translation, replication, assembly, production, and infectivity (28,49,50). The presence of the TC tag allows the tagged HCV core protein in the cells or in HCV to be detected live by microscopic imaging through its covalent binding to the cell membrane-permeant nonfluorescent biarsenical compound and its ensuing fluorophore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the Golgi and endocytic pathways intersect and the exit routes from the trans-Golgi network (TGN) also include the early, late, and recycling endosomes (15,16). A recent study applying siRNA screening highlights the importance of ER-Golgi trafficking in HCV secretion, as well as lipid and protein kinases that function in TGN cargo vesicle budding (17). Rab11A, a small GTP binding protein that modulates trafficking from recycling endosomes and the Golgi and PI4KIII␤, a PI4-kinase localized to the Golgi were shown to be required for HCV virion secretion (17).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Rab11a-positive recycling endosomes sort some vesicles to define the directions during exocytosis (41,42). Hepatitis C virus particles are localized in recycling endosomes transiently and the recycling endosomes serve as a sorting station (43). We found that WNV particles colocalized with Rab11-and transferrin-positive recycling endosomes in infected cells.…”
Section: Discussionmentioning
confidence: 74%